A New Method to Obtain the Complete Genome Sequence of Multiple-Component Circular ssDNA Viruses by Transcriptome Analysis - Yu, Nai-tong; Zhang, Yu-liang; Wang, Jian-hua; Liu, Zhi-xin (Frontiers in Bioengineering and Biotechnology, 2020)
Circular single-stranded DNA (ssDNA) viruses are widely distributed globally, infecting diverse hosts ranging from bacteria, archaea, and eukaryotes. Among these, the genome of Banana bunchy top virus (BBTV) comprises at least six circular, single-stranded DNA components that are ~1 kb in length. Its genome is usually amplified and obtained at the DNA level. However, RNA-based techniques to obtain the genome sequence of such multi-component viruses have not been reported. In this study, transcriptome sequencing analysis showed that the full-length of BBTV each genomic component was transcribed into viral mRNA (vmRNA). Accordingly, the near-complete genome of BBTV B2 isolate was assembled using transcriptome sequencing data from virus-infected banana leaves. Assembly analysis of BBTV-derived reads indicated that the full-length sequences were obtained for DNA-R, DNA-U3, DNA-S, DNA-M, DNA-N, NewS2 and Sat4 components, while two gaps (73 and 25 nt) missing in the DNA-C component which was further filled by reverse transcription-PCR (RT-PCR). The RT-qPCR analysis indicated that the vmRNA levels of coding regions were 3.19–103.53 folds higher than those of non-coding regions, implying that the integrity of genome assembly depended on the transcription level of non-coding region. In conclusion, this study proposes a new approach to obtain the genome of nanovirids, and provides insights for studying the transcriptional mechanism of the family Nanoviridae, Genomoviridae and Geminiviridae.